2010
DOI: 10.1055/s-0030-1250435
|View full text |Cite
|
Sign up to set email alerts
|

PPARαActivation by Culinary Herbs and Spices

Abstract: Hyper- and dyslipidemia are risk factors for cardiovascular disease, the primary cause of death in industrialized countries. Peroxisome proliferators-activated receptor (PPAR)α activation is involved in various mechanisms that improve the lipid profile. We tested various plant extracts and their compounds to determine whether they stimulated PPARα activity in vitro. Out of 34 tested plant extracts, nine exhibited low to moderate PPARα transactivation, including caraway, chili pepper, nutmeg, licorice, black an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
1
24
0
1
Order By: Relevance
“…PPAR agonists such as fibrates could improve the metabolic disorders including high TG level, high glucose level, insulin resistance, and atherosclerosis . Therefore saffron through PPARα activation can improve the lipid profile …”
Section: Effects On Dyslipidaemiamentioning
confidence: 99%
“…PPAR agonists such as fibrates could improve the metabolic disorders including high TG level, high glucose level, insulin resistance, and atherosclerosis . Therefore saffron through PPARα activation can improve the lipid profile …”
Section: Effects On Dyslipidaemiamentioning
confidence: 99%
“…Spices are effective and powerful preventative agents because they modify risk factors associated with CVD, including raised cholesterol and triglyceride levels, high blood pressure, sticky platelets, and chronic systemic inflammation. Caraway, chili pepper, nutmeg, licorice, black pepper, white pepper, paprika, coriander, and saffron all exhibit low to moderate PPARα transactivation, which helps to improve the lipid profile and reduce the risk of CVD (Mueller et al, 2011). In addition, curcumin was shown to inhibit CRP-induced PAI-1 mRNA expression in human endothelial cells, thereby indicating its cardioprotective properties (Chen et al, 2008).…”
Section: Dietary Agents Inflammation and Chronic Diseasesmentioning
confidence: 99%
“…Recent research has shown that capsaicin activates PPARα in vitro with an EC 50 of 50 μM (Mueller et al 2011). In addition, dietary capsaicin enhances fatty acid oxidation in adipose tissue through PPARα activation (Kang et al 2010).…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%